Pengabdian Masyarakat dalam Bidang Hukum: Program Pendidikan Hukum untuk Anak-anak Muda di Kelurahan Gersik - L. M. Zainul; Muhammad Firdaus Pratama; Ronaaziyyah Tanjung; Sophia Diana Putri; Ziad Nazila Nakil Udhma; Dhani Alamsyah; Muftya Ul Lathifa; M. Irsyad Al Mutawaqil; Narendra Jalanidi; Selvia Indah Sari; Welem Yahya Tarul Allo (Abdimas Universal, 2024)
This article discusses a community program carried out in the Gersik Village area in the legal field as a solution to the problems faced by young people in the area. The article explains the basis for the selection of the community service program, the methodology chosen in its implementation, and the preparations needed before the program began. This program aims to introduce aspects of legal education to young people in Gersik Village as an effort to solve the legal problems they face. The implementation of this program is carried out through various activities which include providing materials, group discussions, and simulating legal cases. After the program was completed, an evaluation of the results achieved was carried out to evaluate the success of this community service program in solving legal problems in Gersik Village. This article was prepared based on facts in the field and experiences from the implementation of the community service program in Kelurahan Gersik. Although not perfect, this article provides a concise, factual, and straightforward description of the program. The results of this program are expected to provide real benefits for young people in Gersik Village and become an inspiration for similar programs in other areas.